2020
DOI: 10.1155/2020/8862813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forest Management Types on Soil Carbon Stocks in Montane Forests: A Case Study of Eastern Mau Forest in Kenya

Abstract: Mau Forest, a major forest reserve in Kenya, has experienced anthropogenic disturbances through encroachment and forest fires. This study aimed at comparing the soil carbon stocks in different forest management types as well as how seasonal climatic changes influence its dynamics. The study was undertaken in the Eastern Mau block (Sururu) which forms part of the greater Mau Forest Complex. The forest management interventions have been in place for over 15 years with disturbed (fire) natural forest experiencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…There are a number of studies that have determined patterns of tree species composition and diversity in different forest ecosystems globally, emphasizing the determination of floristic similarity and diversity gradients [35,36]. Similar studies have been reported in the Kakamega tropical rain forest [37] and Mau Forest in Kenya [38], among others. Studies on the woody species composition, the tree diversity and the regeneration status of Londiani Forest, which is a montane forest, are lacking.…”
Section: Introductionsupporting
confidence: 61%
“…There are a number of studies that have determined patterns of tree species composition and diversity in different forest ecosystems globally, emphasizing the determination of floristic similarity and diversity gradients [35,36]. Similar studies have been reported in the Kakamega tropical rain forest [37] and Mau Forest in Kenya [38], among others. Studies on the woody species composition, the tree diversity and the regeneration status of Londiani Forest, which is a montane forest, are lacking.…”
Section: Introductionsupporting
confidence: 61%
“…However, in an unmanaged forest, forest fire always imbibes aboveground biomass and forest floor carbon, and based on the extent of the fire, belowground roots and soil carbon may be adversely impacted (Joshi et al, 2020). Tarus and Nadir (2020) predicted that when exposed to excessive fire, the carbon retained in the forest floor litter and branches undergoes prompt oxidation, permitting it to transfer to a gaseous phase.…”
Section: Discussionmentioning
confidence: 99%
“…Soil biota drive interaction between soil function, environment, and human activities to further boost C sequestration and build healthy soils and environment [50,85]. Sustaining forest ecosystems through introduction nitrogen-fixing species such as acacias [20,35,48] or managing organic residues [43,44] had a tremendously positive impact on both forest productivity and soil attributes [18,19,42,44,91].…”
Section: Sustainable Development Goal 15 Of 'Life On Land'mentioning
confidence: 99%